Assessing environmental sustainability in top Middle East travel destinations: insights on the multifaceted roles of air transport amidst other energy indicators - Onifade, Stephen Taiwo; Haouas, Ilham (Springer, 2023)
The Middle Eastern region is well-known for its flourishing tourism industry as the aviation sector contributes over US$213 billion to the regional GDP while air transport-related activities account for over 3.3 million jobs. Howbeit, the environmental impacts of this flourishing industry remain questionable. Hence, this study examines the tourism-emissions nexus in the Middle Eastern region from the perspective of air transportation while underscoring the multifaceted roles of major indicators like globalization, income, and energy use in the region. The empirical analysis of data spanning from 1975 to 2018 was conducted with advanced panel data analytical approach using the CS-ARDL technique. The sample selection was guided by available statistics on international tourist arrivals from the United Nations World Tourism Organization (UNWTO 2020), with a focus on the case of the five leading travel destinations in the region including Saudi Arabia, the United Arab Emirates (UAE), Egypt, Oman, and Qatar. The robustness of the evaluated outputs was checked after which result-based policy suggestions were enunciated for authorities and other regional stakeholders. The analysis indicated that air transportation although boosting tourism has constituted significant detrimental environmental impacts on the reviewed destinations with an estimated long-run elasticity of ∼1.03. Additionally, while the trio of globalization, energy utilization, and income expansion exacerbate environmental degradation, the lowest carbon-triggering magnitude was observed from the regional income expansion. Thus, while the aviation sector facilitates the growing quest to diversify from a primary sector-based economy (mainly resources exploitation) to other prospective service industries like tourism, the study posits the need for authorities to put measures in place to address the environmental side effect of air transportation.
Keywords: Air transport; Environment; Energy consumption; Globalization; The Middle East; tourism; fi=Taloustiede|en=Economics|